Indian Classical Music: Cultural Syncretism and Its Role in Shaping Societal Norms in India - Dr. Sangeeta (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
Indian classical music, with its rich tapestry of sounds, modes, and rhythms, stands as a testament to the cultural diversity and depth of India. This musical tradition, spanning thousands of years, has not only survived the test of time but has thrived, evolving into a complex system of ragas and talas that resonate with the soul of India. The evolution of Indian classical music is a story of cultural syncretism, where various influences—local, regional, and foreign—have been absorbed, adapted, and reinterpreted to create something uniquely Indian. This research paper aims to explore the trajectory of Indian classical music's evolution, emphasizing its role in cultural syncretism and its impact on shaping societal norms in historical India